Assessing the influnce of self-reported requirement importance on the perceived quality of proposed software products - Hussain, Azham; Mkpojiogu, Emmanuel O.C. (2016)
Customer satisfaction is highly associated with product quality.The perceived quality of products serves as a driver for the loyalty of customers and also promotes high profitability, viability of products and return on investment. Therefore, understanding the importance of requirements as it is associated with the satisfaction of users or customers when their requirements are fulfilled is worth the stress considering.So many studies have been done on customer satisfaction in relation to the importance of requirements, but the correlation between customer satisfaction coefficients of the Kano model and users or customers reported requirements importance have not been sufficiently examined. In this study, an attempt is made to investigate the influence of customer reported requirements importance on the perceived quality of proposed software products. The result of the study indicates a significant relationship between the reported requirement importance and perceived quality of proposed software products. Since customer satisfaction (perceived quality) is directly related to the reported requirements importance, it is therefore essential to give adequate place to user or customer satisfying the requirements (features) all through the software development lifecycle as this enhances the products perceived quality.